Anatomy of Old Faithful From Subsurface Seismic Imaging of the Yellowstone Upper Geyser Basin. Issue 20 (21st October 2017) - Wu, Sin‐Mei; Ward, Kevin M.; Farrell, Jamie; Lin, Fan‐Chi; Karplus, Marianne; Smith, Robert B.
Abstract: The Upper Geyser Basin in Yellowstone National Park contains one of the highest concentrations of hydrothermal features on Earth including the iconic Old Faithful geyser. Although this system has been the focus of many geological, geochemical, and geophysical studies for decades, the shallow (<200 m) subsurface structure remains poorly characterized. To investigate the detailed subsurface geologic structure including the hydrothermal plumbing of the Upper Geyser Basin, we deployed an array of densely spaced three‐component nodal seismographs in November of 2015. In this study, we extract Rayleigh wave seismic signals between 1 and 10 Hz utilizing nondiffusive seismic waves excited by nearby active hydrothermal features with the following results: (1) imaging the shallow subsurface structure by utilizing stationary hydrothermal activity as a seismic source, (2) characterizing how local geologic conditions control the formation and location of the Old Faithful hydrothermal system, and (3) resolving a relatively shallow (10–60 m) and large reservoir located 100 m southwest of Old Faithful geyser. Key Points: We seismically image Yellowstone's iconic hydrothermal system utilizing stationary hydrothermal activity as a seismic source We constrain how shallow geologic structure and fluid pathways control the formation and location of Old Faithful geyser and the Upper Geyser Basin hydrothermal system We image a relatively large and shallow, 10‐60 m, 200 m wide hydrothermal reservoir centered 100 m southwest of Old Faithful geyser